Dynamic Measurement of Flowing Microparticles in Microfluidics Using Pulsed Modulated Digital Holographic Microscopy - Yunze Lei; Yuge Li; Xiaofang Wang; Kequn Zhuo; Ying Ma; Sha An; Juanjuan Zheng; Kai Wen; Lihe Yan; Peng Gao (Photonics)
We propose a pulsed modulated digital holographic microscopy (PM-DHM) technique for the dynamic measurement of flowing microparticles in microfluidic systems. By digitally tuning the pulse width and the repetition rate of a laser source within a single-frame exposure, this method enables the recording of multiple images of flowing microparticles at different time points within a single hologram, allowing the quantification of velocity and acceleration. We demonstrate the feasibility of PM-DHM by measuring the velocity, acceleration, and forces exerted on PMMA microspheres and red blood cells flowing in microfluidic chips. Compared to traditional frame-sampling-based imaging methods, this technique has a much higher time resolution (in a range of microseconds) that is limited only by the pulse duration. This method demonstrates significant potential for high-throughput label-free flow cytometry detection and offers promising applications in drug development and cell analysis.